Risk and Protective Processes Predicting Rural African American Young Men's Substance Abuse. Issue 3 (23rd November 2016) - Cho, Junhan; Kogan, Steven M.
Abstract: Informed by a life course perspective, this study tested a cascade model linking harsh, unresponsive parenting during childhood to young African American men's substance abuse via precocious transitions, economic instability, and future orientation. The moderating influence of community disadvantage and romantic partner support on the hypothesized pathways was also examined. At the baseline, the sample included 505 African American men between ages 19 and 22 years from high‐poverty rural communities. Follow‐up data were collected 18 months after baseline. Using structural equation modeling, we identified harsh, unresponsive parenting influenced precocious transitions in adolescence, which in turn increased economic instability during young adulthood. Economic instability was associated with a reduction in future orientation, a proximal influence on increases in substance abuse. Also, residence in a disadvantaged community amplified the influence of precocious transitions on economic instability and the influence of economic instability on future orientation. Involvement with supportive romantic partnership evinced a protective effect, attenuating the influence of precocious transitions on economic instability and the influence of economic instability on a future orientation. This study expands understanding of young adults' substance abuse by demonstrating the risk and protective processes linking substance abuse to developmental factors across childhood, adolescence, and young adulthood.